ANALISIS KESANTUNAN BERBAHASA DALAM NOVEL SI ANAK KUAT KARYA TERE LIYE: KAJIAN PRAGMATIK - Agustina, Shella; Amir, Amriani; Jupitasari, Mellisa (Universitas Tanjungpura, 2024)
This research aims to describe language politeness clearly and in detail in the novel Si Anak Kuat by Tere Liye: a pragmatic study. The method used in this research is descriptive in qualitative form. The data source in this research is Tere Liye. The data collection technique used is the documentary study technique, the documentary study technique is a data collection technique through document collection and analysis. The documents obtained are then analyzed, compared and integrated (synthesized) to form a systematic, comprehensive and complete study. including written documents, drawings, compositions and electronic documents. The documentary study technique is carried out by collecting data related to language politeness. Based on the results of research analysis, 71 maxims of language politeness were found, namely 16 maxims of wisdom, 12 maxims of generosity, 15 maxims of respect, 9 maxims of simplicity, 10 maxims of consensus, and 10 maxims of sympathy. Politeness analysis uses pragmatic studies according to Leech's theory.